A Study of the Soviet Economy : 3-Volume Set. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1991)
This three-volume study of the Soviet economy presents the detailed information, analysis, and recommendations for the summary report presented to the Group of Seven industrial countries in December 1990. The study was prepared by staff members of the IMF, the World Bank, the OECD, and the EBRD.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Economic Development; Housing; Industry Studies; Infrastructure; Labor Economics